IN VITRO PROPAGATION OF JATROPHA CURCAS FROM EMBRYO AND NODAL EXPLANTS - G. D. RAM; S. S. CHAUHAN; D. K. VERMA (The Bioscan, 2012)
In vitro propagation of Jatropha curcas was established from embryo and node cultures of the field grown plants on Murashige and Skoog’s medium supplemented with different composition of growth regulators i.e. Benzylaminopurine (BAP), Naphthalene acetic acid (NAA), and Indole-3-butyric acid (IBA). The modified MS medium BAP (3.0 mg/L) and IBA (1.0 mg/L) induced regeneration of maximum number of shoots (5-6±1.48), whereas the maximum callus and shoot buds (5-6±2.1) were produced on BAP (1.5 mg/L) and IBA (1.0 mg/L). The rooting and plantlet establishment were observed at IBA (3.0 mg/L) with maximum survival rate (95%).